2021
DOI: 10.1177/17455065211043844
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis in immunocompetent Saudi women: Correlation with vitamin D

Abstract: Objective: Toxoplasma gondii ( T. gondii) is a life-threatening parasite particularly infecting the immunocompromised women. Deficiency of vitamin D is well reported in several infectious disorders. This study was undertaken to investigate a correlation of vitamin D deficiency with the onset of T. gondii infection in immunocompetent women from the central of Saudi Arabia. Methods: Blood samples were collected from 304 Saudi women from the Qassim region of Saudi Arabia. Specific immunoassays were used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The conclusions in studies of the association between vitamin D levels and T. gondii antibody seroprevalence have been controversial [18]. Two studies with small sample sizes have reported that vitamin D deficiency increases the risk of T. gondii infection [18,19]. However, another study with three cohorts and a larger sample size (n=663) has rejected this hypothesis [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions in studies of the association between vitamin D levels and T. gondii antibody seroprevalence have been controversial [18]. Two studies with small sample sizes have reported that vitamin D deficiency increases the risk of T. gondii infection [18,19]. However, another study with three cohorts and a larger sample size (n=663) has rejected this hypothesis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency, which is common in the general population [10,11], has been found to increase susceptibility to some infections, such as human papillomavirus, latent tuberculosis, COVID-19 and acquired immune deficiency syndrome [12][13][14][15]. In vitro and in vivo studies have demonstrated a protective role of vitamin D against T. gondii infection [16,17]; however, the results regarding the relationship between vitamin D status and T. gondii infection in humans have been contradictory [18][19][20]. The present study aimed at exploring the relationship between vitamin D levels and T. gondii infection, on the basis of a nationally representative database.…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasmosis has been correlated with many diseases 5 . A study detected vitamin D deficiency during acute toxoplasmosis episodes 6 . Another study found a correlation between the rising titer of Toxoplasma IgG and levels of vitamin D 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A study detected vitamin D deficiency during acute toxoplasmosis episodes 6 . Another study found a correlation between the rising titer of Toxoplasma IgG and levels of vitamin D 6 . Regarding rubella, one study detected no correlation between vitamin D and rubella 7 .…”
Section: Introductionmentioning
confidence: 99%